Clinical Characteristics and Risk Factors of In-Hospital Mortality in Patients With Acute Myocardial Infarction With Subsequent Gastrointestinal Bleeding: A Single-Center Experience - Su, Xin; Wei, Yuzhen; Pang, Shuo; Zhang, Zeqing; Zhang, Yunxiao; Zheng, Peipei; Li, Haiyu; Sang, Haiqiang; Dong, Jianzeng (Frontiers in Cardiovascular Medicine, 2022)
Objective: Gastrointestinal bleeding (GIB) post acute myocardial infarction (AMI) is a severe clinical condition with a poor prognosis. The purpose of the study was to evaluate the rate of in-hospital mortality in patients with GIB post-AMI and to identify the potential risk factors of this situation. Methods: In this single-center retrospective study, a total of 154 patients diagnosed with AMI who subsequently suffered GIB were enrolled from October 2013 to December 2021. Demographic, laboratory, and clinical data were collected. The in-hospital mortality was the outcome of interest. Logistic regression analysis was used to investigate the potential risk factors of in-hospital mortality. Results: Among the 154 subjects included in the final analysis, the mean age was 65.58±11.20 years, and 104 (67.53%) were males. GIB occurred in 11 patients after thrombolytic therapy, 50 patients after percutaneous coronary intervention (PCI), and 93 patients during drug conservative treatment. A total of 41 patients died in the hospital. The in-hospital mortality rate of the thrombolysis group, PCI group, and drug conservative treatment group was 27.27% (3/11), 28.00% (14/50), and 25.81% (24/93), respectively. There was no difference in the in-hospital mortality among the three groups. The multivariate logistic regression analysis showed that the peak levels of TnI (OR 1.07, 95%CI 1.02-1.12, P=0.011), condition of cardiogenic shock after admission (OR 14.52, 95%CI 3.36-62.62, P< 0.001), and the use of the mechanical ventilator (OR 8.14, 95%CI 2.03-32.59, P=0.003) were significantly associated with in-hospital mortality. Conclusions: Regardless of the treatment strategy for AMI, once GIB occurred, the prognosis was poor. High in-hospital mortality in patients with GIB post-AMI was independently associated with the peak levels of TnI, condition of cardiogenic shock, and the use of a mechanical ventilator.